Estimation of water vapour weighted atmospheric mean temperature in support of GPS meteorology for Peninsular Malaysia [electronic resource] - Muhammad Faiz Norazmi, 1989-, author 638832 (2012)
Project Paper (Sarjana Muda Kejuruteraan (Geomatik)) - Universiti Teknologi Malaysia, 2012